An integrated model of IPSAS institutionalisation in Indonesia: a critical study. Issue 2 (24th December 2020) - Harun, Harun; Eggleton, Ian R.C.; Locke, Stuart
Abstract : Purpose: The aim of this study is to critically evaluate the institutionalisation of International Public Sector Accounting Standards in Indonesia. Design/methodology/approach: This case study approach relies on obtaining its data from document sources and interviews with relevant people and/or organisations involved in policy-making and implementation of IPSAS in Indonesia. To inform the study, we developed and used an integrated model of institutionalisation based on the work done by Dillard et al . (2004) and Dambrin et al. (2007). Findings: Our model shows that dissemination of new ideals and the transformation of these new ideals into new discourses were institutionalised at the economic and political level. However, the creation of a new [accounting]technique took place in the organisational field, instead of organisational level. The internalisation of IPSAS in the organisational field is characterised by limited use of IPSAS-based reports for making decisions. Overall the institionalisation of IPSAS in Indonesia is dominated by actors external to local governments. Research limitations/implications: The study's results reflect the specific socio-economic and political contexts for a specific point in time. Practical implications: Policy-makers in developing nations should consider the applicability of IPSAS in accordance with the actual needs and capacities of their local governments. Social implications: The findings show that developing nations and international organisations have underestimated the technical and institutional issues of developing nations in the globalisation of IPSAS. Originality/value: The study extends institutional theory by developing a new model to conceptualise the dynamic processes, the role of actors and outcomes of public sector accounting reforms in an emerging economy.